PERSONIFICATION USED IN WDDING-THEMED SONG LYRICS - Viktoria vabiola Dea solambela; Ignatius J. C. Tuerah; Tirza A. Kumayas (Program Studi Pendidikan Bahasa Inggris, 2023)
This study looked for personification expressions and the many kinds that might be found in wedding-related music lyrics. This study used the descriptive technique. Only the personification expressions in the lyrics of well-known songs with wedding themes were the subject of this investigation. Only songs that were released between 2010 and the present were used by the researcher as sources of data. Dodson (2008) combined the data, classified them according to linguistic theory, then conducted an analysis and interpretation. The research reveals that twenty personification data were discovered in song lyrics with wedding-related themes. Six of the phrases are categorized as casual personification (30%), nine are categorized as broad personification (45%), and the remaining five are representational personification (which account for 25% of the total). The most common sort of personification in lyrics is type 2, whereas type 3 is the least common. Most often, the purpose of utilizing personification phrases is to embellish or beautify the song lyrics itself so that they are attractive to the audience and attractively convey the content to the song listeners. Figurative language is a useful technique for improving song lyrics since song lyrics have the ability to convey messages to listeners about life, love, and a variety of other topics. The lyricist becomes more lyrical and the phrases gain strength by employing metaphorical language. In the course of teaching literature and linguistics, it is suggested that personification, which is frequently utilized in song lyrics.